(untitled) (KONFERENSIYA, 2025)
Motivation plays a crucial role in effective foreign language acquisition, particularly in higher education, where students encounter academic demands, digital diversions, and varying learning styles. This research explores creative teaching approaches that boost language learning motivation in university students. The study outlines five primary motivational strategies: gamification, mobile-assisted language learning, flipped classroom, AI-supported task-based learning, and project-based learning. Results show that interactive, technology-enhanced, and autonomy-focused methods significantly increase learners’ engagement, intrinsic motivation, and persistence. The findings highlight the importance of integrating modern educational technologies with communicative, student-centered teaching approaches